Development of the VIRAH Website Based on 3D Augmented Reality for Asmaul Husna Learning in Grade 6 Elementary School - Ani Nur Aeni; Jainatul Halida Jaidin; Dinda Sarasikha; Farah Lestari; Naila Nursifa Rohmah (Jurnal Pendidikan Progresif, 2026)
The Teaching of Asmaul Husna in elementary schools remains dominated by memorization. This approach struggles to translate abstract religious concepts into concrete representations suitable for students’ concrete operational stage of cognitive development.  This study aims to develop and evaluate a website-based technology named VIRAH (Visualization Interactive Asmaul Husna 3D AR), as an interactive learning technology for sixth-grade students in Islamic Education. The research employed the Design and Development (D&D) method following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The resulting product is the VIRAH website, which integrates Augmented Reality (AR) technology using the Assemblr Edu platform and is published via Netlify.  The website was validated by subject matter and media experts, then implemented with 27 sixth-grade students at SDN Sukaraja II, Sumedang. Data collection utilized validation sheets, student response questionnaires, and pretest-posttest instruments. Data analysis was conducted using percentage calculations, the N-Gain Score, a paired t-test, and effect size calculations. The validation results showed that the media received a score of 93.75% from subject matter experts and 98.13% from media experts, both of which fell into the “highly acceptable” category. The average N-Gain Score of 0.64 falls into the “moderately effective” category. The paired t-test confirmed a statistically significant increase (t = 7.97; df = 26; p < 0.05), with an effect size of d = 1.766, classified as “very large”. The student response questionnaire yielded a positive percentage of 77.04%, categorized as “good”. In conclusion, the development of the VIRAH website, based on 3D AR technology, is proven feasible and sufficiently effective in enhancing elementary students' understanding of Asmaul Husna. It successfully transforms abstract concepts into concrete, interactive, and meaningful learning experiences. Keywords: 3D augmented reality, VIRAH website, interactive learning technology, asmaul husna, elementary school.